High performers - Dubinsky, Alan J. (Thomson South-Western, 2004)
Dubinsky and Skinner have uncovered 13 drivers of discretionary effort, or why employees go above and beyond what is expected of them in the job. If you are aware of these drivers, and if you use their prescription to recruit, manage and retain employees with these attributes, you can realize a company of High Performers